2020
DOI: 10.1177/0907568220909430
|View full text |Cite
|
Sign up to set email alerts
|

Repertoires on diversity among primary school children

Abstract: This article examines how children in super-diverse schools draw on cultural repertoires to construct ethno-cultural similarities and differences. Based on 47 interviews, we show how, first, children talk about diversity as a commonplace aspect of daily life. Second, we describe how cosmopolitan arguments are used to make sense of diversity. The third repertoire focusses on ‘otherness’ and emphasizes the ‘cultural frictions’ that would stem out of diversity. Finally, we describe how some children share a stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
(46 reference statements)
0
8
0
1
Order By: Relevance
“…How do youth navigate peer relations and everyday interactions within a super-diverse context? Most respondents, as illustrated by Mauro’s account, draw on a cultural repertoire of commonplace diversity (Albeda et al, 2018; Kostet et al, 2021; Wessendorf, 2014). Mauro (ethnic majority, school 2): “I get along with everyone.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…How do youth navigate peer relations and everyday interactions within a super-diverse context? Most respondents, as illustrated by Mauro’s account, draw on a cultural repertoire of commonplace diversity (Albeda et al, 2018; Kostet et al, 2021; Wessendorf, 2014). Mauro (ethnic majority, school 2): “I get along with everyone.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we have shown how ethnic majority and minority youth in a super-diverse city and school context blur group boundaries by applying a cultural repertoire of commonplace diversity and stress the normalcy and coolness of their super-diverse peer relations and school context (Kostet et al 2021; Wessendorf, 2014). However, a more in-depth analysis revealed how ethnic and religious symbolic boundaries emerge as bright, where minority youth need to navigate othering and social exclusion processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They thus defined social justice as the ‘natural’ acceptance of our human commonalities above and beyond any other characteristics. Our findings mirror Kostet et al .’s (2020) research findings that some children make the choice not to place emphasis on ethnic, cultural or religious differences as they view diversity as ‘commonplace’. In their research focusing on the repertoires of diversity among primary school children, they inter alia found that ‘ethno‐cultural diversity is not always highly relevant for some children’, which was ‘also evidenced by the lack of spontaneous references to this form of diversity’ (Kostet et al ., 2020: 8).…”
Section: Resultsmentioning
confidence: 99%